Major global radiation of corvoid birds originated in the proto-Papuan archipelago - Jønsson, Knud A.; Fabre, Pierre-Henri; Ricklefs, Robert E.; Fjeldså, Jon (Proceedings of the National Academy of Sciences - PNAS, 2011)
A central paradigm in island biogeography has been the unidirectional "downstream" colonization of islands from continents (source to sink) based on the idea that less-diverse island communities are easier to invade than biologically more-diverse continental communities. Recently, several cases of "upstream" colonization (from islands to continents) have been documented, challenging the traditional view. However, all these cases have involved individual island species that have colonized mainland regions. Here, using molecular phylogenetic data, divergence time estimates, lineage diversity distributions, and ancestral area analyses, we reconstruct the spread of a species-rich (> 700 species) passerine bird radiation (core Corvoidea) from its late Eocene/Oligocene origin in the emerging proto-Papuan archipelago north of Australia, including multiple colonizations from the archipelago to Southeast Asia. Thus, islands apparently provided the setting for the initiation of a major songbird radiation that subsequently invaded all other continents. Morphological and behavioral adaptations of the core Corvoidea as generalist feeders in open habitats, which facilitated dispersal and colonization, apparently evolved in the descendants of sedentary forest birds that invaded the proto-Papuan archipelago. The archipelago evidently provided islands of the right size, number, and proximity to continental areas to support the adaptation and diversification of vagile colonizers that went on to increase avian diversity on a global scale.